2009
DOI: 10.1590/s0036-46652009000100003
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of toxoplasmosis in women of childbearing age from a marginal community of Maracaibo, Venezuela

Abstract: SuMMarYThe aim of this study was to determine the prevalence of anti-T. gondii total and IgM antibodies in women of childbearing age. One hundred serum samples of women were studied with age range from 11 to 45 years old. Samples were chosen by random. The determination of total antibodies was carried out through the indirect hemagglutination technique and IgM antibodies by ELISA's technique. The statistical analysis was carried out through the Chi square and the Spearman correlation tests. The theoretical est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 18 publications
2
13
1
5
Order By: Relevance
“…About prevention, although 42.5 % of professionals recognize avoid contact with cat faces is the most commonly used method for preventing the spread and transmission of toxoplasmosis, which is similar to other studies [DIAZ-SUAREZ, 2009. AKYAR, 2011 .…”
Section: Diagnosis Of Toxoplasmosissupporting
confidence: 74%
“…About prevention, although 42.5 % of professionals recognize avoid contact with cat faces is the most commonly used method for preventing the spread and transmission of toxoplasmosis, which is similar to other studies [DIAZ-SUAREZ, 2009. AKYAR, 2011 .…”
Section: Diagnosis Of Toxoplasmosissupporting
confidence: 74%
“…The comparison of the seropositivity of the pregnant women in Divinópolis with the prevalence of toxoplasmosis in other countries showed that the number of cases found in this study is twice that diagnosed in the Palestine (27.9%) 6 , 4 times higher than in China (12.3%) 2 , and also higher than in Venezuela (33%) 1 . In contrast, the numbers found were similar to the prevalence found in rural populations of France (47%) 4 , Albania (48.6%) 5 , and rural (57.6%) and urban (46.5%) areas of Egypt 6 .…”
Section: Discussionmentioning
confidence: 43%
“…15 However, other studies among Taiwan indigenous people have reported a lower seroprevalence of 19.4% to 21.8% in Atayal, 16 26.7% in Paiwan, 17 and 9.1% in Akka 17 subgroups. In contrast, seroprevalence rates among indigenous people in Brazil 18 and Venezuela [19][20][21][22][23] have been relatively high: 73.5% and up to 88.0%, respectively. This global status on T. gondii infection indicates that, although these minority people stay in different geographical locations, they still experience similar poor sanitary living conditions.…”
Section: Discussionmentioning
confidence: 99%
“…12 This finding was also consistent with other studies reported from Taiwan 1 and Venezuela. 21,23 Based on the overall results obtained, these indigenous communities were possibly exposed to the infection through T. gondii oocysts excreted from infected cats that contaminate soil. Therefore, it is imperative to promote awareness of this parasitic infection through educating this community on the importance of collecting cats' feces in litter boxes, discarding them properly, spaying cats to reduce overpopulation, and most importantly, washing hands before eating, after gardening, and after contact with soil.…”
Section: Discussionmentioning
confidence: 99%